Copyright from Inside the Box: A View from the U.S. Copyright Office*: Keynote Address - Kasunic, Robert (The Columbia Journal of Law & the Arts, 2016)
Good morning. I want to thank Professors Ginsburg and Besek for inviting me to speak today and introducing me. I also want to thank everyone at the Kernochan Center and the Journal of Law and the Arts for their assistance. It’s always a pleasure to be here—a block from where I grew up. And an entire event about copyrightability, what a wonderful thing. This topic is usually covered in just a couple minutes in a panel, but I really want to welcome you to my world at the U.S. Copyright Office. I’d also like to take a moment for a pitch for a twenty-first century Copyright Office as well. This is a picture of the Office as it appeared in the 1920s, so we are actually not still using typewriters. This is a more current view of my office that, on a daily basis, examines more claims than the federal courts review in any given year. The issues that come up are enormously varied and complex. But where we start our assessment of copyrightability in the Office is where we start when we first begin studying copyright law, and where we start when we’re teaching copyright with our students—back to the basic principles of copyright, and some of the seminal cases on creativity.